A homozygous loss-of-function mutation leading to CYBC1 deficiency causes chronic granulomatous disease - Gudny A. Arnadottir (Nature Portfolio, 2018)
Mutations in genes encoding NAPDH oxidase subunits are known to be causative for the primary immunodeficiency chronic granulomatous disease (CGD). Here, the authors identify CYBC1 mutations in patients with CGD and show that CYBC1 is important for formation of the NADPH complex and respiratory burst.